The Improving Students’ Writing Descriptive Text by Using Audio Visual at The Grade X SMA Negeri 1 Portibi - Ritonga, Rahma Yunisa (jurnalalfa, 2025)
The aims of this research is to improve students’ descriptive text at the grade X SMA Negeri 1 Portibi. The researcher used classroom action research as a method of the research. The researcher used purposive sampling at the grade X with the sample were 23 students. The object of this research was students at the grade X of SMA Negeri 1 Portibi. The researcher gave a pre-test namely to write a descriptive text about tourist attraction, then the researcher teaching the students by using audio visual about descriptive text, researcher gave a post-test to get the comparison, then interviewed and gave a questionnaire to get accurate results in this study there were 23 students as researcher sample. The result of this research is the students improve value, where the total of score of students in cycle 1 is 54, 9% whereas in cycle II 72, 1%. So, the researcher concluded that using audio visual can improve the students’ writing descriptive text. The difficulties of students in writing descriptive text are in mechanical that is the lowest score of students, on mechanical students are still often wrong in spelling then content, organization, vocabulary and the last grammar.